Factors Influencing Community Decisions in Choosing Community Health Centers for Promotive and Preventive Health Services: Literature Review - Lailatul Hasanah; Nurul Fitriyah; Rosalia Nindy Prastika Sari; Diansanto Prayoga (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Minister of Health Regulation Number 43 of 2019 stated that Community Health Centers (Puskesmas) were health service facilities that provided community health efforts (UKM) and individual health efforts (UKP) at the first level, prioritizing promotive and preventive efforts in their working areas. The reason for composing this article was crucial, as Community Health Centers, as both general health services and providers of promotive and preventive services, were expected to attract public interest.. Objective: Analyzed factors influencing community choices of health centers for promotive and preventive services. Method: A qualitative research study was conducted, employing a literature review via electronic databases, particularly utilizing Scopus journal sources. Keywords like "Primary health care," "consumer attraction," and "decision to visit the health center" guided the search, Inclusion criteria set for articles published in English, freely accessible, and between 2019 and 2023. Result: Based on the literature search process through electronic databases, 7 articles were obtained. The selected articles met the predetermined criteria. These articles were related to the use of price transparency tools, community satisfaction and dissatisfaction, the Health Extension Program, the crucial role of good healthcare services, as well as the influence of income and grants. Conclusion: Factors influencing the community's choice of Community Health Centers as a health service included offering lower service costs through insurance or BPJS Kesehatan, the presence of the Health Extension Program (HEP), patient satisfaction with services, gender factors, income, access to grants, and contact with health education.